Contemporary Suicide Terrorism: Origins, Trends and Ways of Tackling It - Dronzina, Tatyana (IOS Press, 2014)
This book consists of research papers presented at the conference “Contemporary Suicide Terrorism: Origins, Trends and Ways of Tackling It” (23th-26th September, 2010). The conference took place in Astana, Kazakhstan, and was hosted by the Faculty of Social Science of Eurasian National University, L.N.Gumilev. It was funded by the NATO Science For Peace and Security Programme (ARW 983898).